2021
DOI: 10.3389/fonc.2021.718815
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography–Based Body Composition in Patients With Ovarian Cancer: Association With Chemotoxicity and Prognosis

Abstract: PurposeTo assess the association between computed tomography (CT)-derived quantitative measures of body composition profiling and chemotherapy-related complications, in terms of dose reduction, premature discontinuation of chemotherapy, and cycle delays in patients with ovarian cancer. Secondary purposes were to evaluate associations between sarcopenia and survival, and to evaluate differences in body composition profiling at baseline and after neoadjuvant chemotherapy.Materials and MethodsThe study population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…The results of this research showed that the effect of the RECIST 1.1 evaluation method was indistinguishable from the CRS grading system in the evaluation of neoadjuvant chemotherapy, indicating that the effect of CT examination evaluation was basically the same as that of pathological examination evaluation, which had a certain practicality. It was consistent with relevant research results [ 19 , 20 ]. In the CT examination results, there were differences in lymphadenectasis, degree of peritoneal thickening, ascites, and maximum length diameter of the mass and were compared between the patients before and after chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this research showed that the effect of the RECIST 1.1 evaluation method was indistinguishable from the CRS grading system in the evaluation of neoadjuvant chemotherapy, indicating that the effect of CT examination evaluation was basically the same as that of pathological examination evaluation, which had a certain practicality. It was consistent with relevant research results [ 19 , 20 ]. In the CT examination results, there were differences in lymphadenectasis, degree of peritoneal thickening, ascites, and maximum length diameter of the mass and were compared between the patients before and after chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…The initial search yielded 812 articles, all in English. According to inclusion and exclusion criteria, 6 full-text articles were included in this systematic review (17,(30)(31)(32)(33)(34). Details about the literature search results are reported in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…On one hand, the assessment of body composition, indicating quantity and distribution of muscle and fat, has been associated with different clinical outcomes of cancer patients, such as tolerance to chemotherapy (7), survival, and postoperative outcomes, including lung cancer (8)(9)(10)(11). On the other hand, lung cancer is being increasingly recognized as a heterogeneous disease in which gender plays a more critical role than previously appreciated in pathogenesis, diagnosis, and treatment (12).…”
Section: Introductionmentioning
confidence: 99%